KAJIAN PENERAPAN IZIN LINGKUNGAN ATAS KEGIATAN WAJIBAMDAL ATAU WAJIB UKL-UPL - Redin Redin (Universitas Kapuas Sintang, 2019)
Legal regulations that can be used to carry out environmental protection from business activities that reject environmental pollution and environmental damage include regulations on Environmental Permits and Environmental Impact Analysis (Amdal). The problem is how to apply environmental permits for EIA-compulsory activities or compulsory UKL-UPL and how to apply legal obligations to EIA compulsory activities or compulsory UKL-UPL that do not have environmental permits. It is known that it is a necessity, Amdal has not been fully adhered to by various parties, including business activities, while this is one of the important requirements to obtain an Environmental Permit. Likewise, it is still an Amdal compulsory activity and the UKL-UPL is not yet compliant with the Amdal or UKLUPL obligations that have been prepared. The application of legal sanctions for Amdal compulsory activities or compulsory UKLUPL that do not have environmental permits has not been carried out maximally. Keywords: Environmental Permit, Amdal, UKL-UPL